The ambivalence of the absurd and the absurd hero in the work of Albert Camus - Provazník, David (Bohemica Olomucensia, 2023)
The presented work deals with the issue of the absurd in the work of Albert Camus. The study deals with the relationship between existential philosophy and literature. The aim is to interpret the novel The Stranger in relation to the basic concepts of Albert Camus. In particular, it is absurd, revolt and resentment. The subject of interest is also the philosophical interpretation of these concepts, which have a fundamental impact on the form of existential literature.
Keywords: Albert Camus; existentialism; French literature; philosophy absurd